Acute toxicity, antibacterial and antioxidant abilities of Elephantopus mollis H.B.K. and Elephantopus scaber L. - Nguyen, Trong Hong Phuc; Do, Tan Khang; Nguyen, Thi Thuy Nhien; Phan, Thanh Dat; Phung, Thi Hang (CTU Journal of Innovation and Sustainable Development, 2020)
Elephantopus mollis H.B.K.,and Elephantopus scaber L. were collected at To mountain in An Giang province and assessed for extraction efficiency, resistance ability to common bacterial strains in humans and animals, antioxidation, and toxicity. The extraction efficiency of two species was 11-26% and 16 – 28%, respectively and depending on the part of the plant. The flowers of both species had better antioxidant results than other parts with EC50 at 32.2051 mg/mL and 59.9778 mg/mL, respectively, which was highly different from the rest of the plant (p). The leaves of both species had higher antibacterial properties than the other parts. For the six bacterial strains tested, both studied species had the strongest inhibiting ability for the growth of E. coli. (at a concentration of 200 mg/mL) different from that of Ampicillin (p). These two species were not toxic to Mus musculus at the dose of 8000 mg/Kg.